2020
DOI: 10.1210/clinem/dgz263
|View full text |Cite
|
Sign up to set email alerts
|

Obese Adolescents With PCOS Have Altered Biodiversity and Relative Abundance in Gastrointestinal Microbiota

Abstract: Context Alterations in gut microbiota relate to the metabolic syndrome, but have not been examined in at-risk obese youth with polycystic ovary syndrome (PCOS). Objective Compare the composition and diversity of the gut microbiota and associations with metabolic and hormonal measures between 2 groups of female adolescents with equal obesity with or without PCOS. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 38 publications
8
119
1
1
Order By: Relevance
“…Upon return to study staff, samples were stored at -80°C until further processing. Bacterial profiles were determined by broad-range analysis of 16S rRNA genes following our previously described methods [ 24 , 31 ]. In brief, DNA was extracted from 50–100 mg of stool using the PowerFecal DNA isolation kit (QIAamp Powerfecal DNA kit (Qiagen INC, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon return to study staff, samples were stored at -80°C until further processing. Bacterial profiles were determined by broad-range analysis of 16S rRNA genes following our previously described methods [ 24 , 31 ]. In brief, DNA was extracted from 50–100 mg of stool using the PowerFecal DNA isolation kit (QIAamp Powerfecal DNA kit (Qiagen INC, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in four predominant gastrointestinal phyla ( Firmicutes , Bacteroidetes , Proteobacteria , Actinobacteria ) have been associated with high fat/low fiber diet, obesity, insulin resistance, T2D, PCOS and NAFLD [ 1 3 , 7 , 20 23 ]. We previously demonstrated that youth with PCOS have a unique microbiota profile relative to similarly obese girls without PCOS [ 24 ]. We thus sought to examine the gut microbiota composition in adolescent girls with combined obesity and PCOS, with or without HS, to determine if there is a unique microbiota profile associated with HS, beyond alterations seen with obesity and PCOS status.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown on broad-spectrum antibiotics-treated endometriosis mice that the FMT from mice with endometriosis resumed the growth of endometriotic lesions suggesting that the gut microbiota could promote endometriosis progression [131]. In humans, differences in gut microbial composition between healthy women and women with endometriosis [152] and polycystic ovary syndrome were reported [153][154][155][156][157][158].…”
Section: Microbial Transplantsmentioning
confidence: 99%
“…Direct interactions of the gut microbiome (GM) and PCOS have been shown in animal model studies [2] . In contrast, the peculiarities of GM associated with PCOS have been studied for female adolescents and women of reproductive years [ 2 , 3 ]. In recent years, pronounced dysbiosis of gut microbial communities has been shown in metabolic diseases (obesity and insulin resistance) associated with PCOS [ 4 , 5 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…Although the search for correlations between the GM and metabolic diseases has become a hot point for recent research, the geography of the studies on PCOS is very narrow and included mainly Chinese studies. A few studies have been carried out in the USA, Austria, and Spain [2] , [3] , [4] , [5] , [6] , [7] , [8] .…”
Section: Data Descriptionmentioning
confidence: 99%